The Impact Of Collectivism And In-Group/Out-Group Membership On The Evaluation Generosity Of Team Members - Gómez, Carolina; Kirkman, Bradley L.; Shapiro, Debra L. (Academy of Management Journal, 2000)
In a scenario-based study using Mexican and U.S. samples, when a team member was perceived to be an in-group (rather than an out-group) member, collectivists evaluated that member significantly more generously than did individualists. Further, collectivists valued maintenance contributions more than individualists did, and individualists valued task contributions more than collectivists did. Nevertheless, both collectivists and individualists appeared to value an equity norm.